Expresiones del ser mujer en el arte contemporáneo colombiano: Una aproximación a las obras de Julieth Morales, Karen Paulina Biswell y Carmenza Banguerra (2023)
The objective of this research is to identify and analyze some expressions of femininity from the plastic and visual production of three Colombian artists: Julieth Morales, Karen Paulina Biswell and Carmenza Banguerra whose works are part of the Art Collection of the Banco de la República between the years 2015–2022.